Control alternative of Powdery mildew in organic blueberry (Vaccinium corymbosum) in Piura, Peru (Agroindustrial Science, 2022)
The objective of the present investigation was to determine the efficacy of twelve alternative treatments for the control of Oidium sp. in blueberry cultivation, under field conditions. The experiment was installed under a randomized complete block design (DBCA). The treatments were proposed based on Bacillus subtilis, AP-01, Bacillus subtilis IAB/BS03, Silicon, Sulfur, Mannan oligosaccharides and potassium bicarbonate. Six treatments in rotation of the mentioned products were considered, and six treatments without rotation. Applications were made weekly, from budding to pre-blooming. The incidence and severity in leaves were evaluated with a frequency of seven days. Then, these variables were transformed to the area under the disease progress curve (AUCPE) for statistical analysis. The results indicate that the treatments with potassium bicarbonate and sulfur had the best incidence control effect with an efficacy of 61.85 and 42.81%, respectively. Likewise, the treatments with potassium bicarbonate, Sulfur and Sulfur in rotation with Silicon appeared the best severity control effect with an efficiency of 73.96, 56.7 and 54.82% respectively.
Keywords: Oidium sp; potassium bicarbonate; sulfur; blueberry; variety Ventura